PENGARUH ONLINE REVIEW RESTORAN PADA WEBSITE PERGIKULINER TERHADAP KEINGINAN UNTUK MEMBELI PRODUK MAKANAN - Bintang Nabila Katya; Imam Syafganti; Christina L. Rudatin (Bisnis Event, 2026)
This study aims to investigate the impact of online restaurant reviews on the PergiKuliner platform on consumer purchase decisions. The objective is to explore the extent to which elements of positive reviews, such as high ratings, descriptive narratives, and food visuals, can influence consumer perceptions and stimulate their purchasing interest. This research employs a quantitative approach, utilizing surveys and simple linear regression analysis to investigate the relationship between the studied variables. The findings are expected to contribute to the development of digital marketing strategies, particularly in the culinary sector. Keywords: Review, Purchase decision, Consumer, Digital marketing